Microstructure, Wetting, and Tensile Behaviors of Sn-Ag Alloy Reinforced with Copper-Coated Carbon Nanofibers Produced by the Melting and Casting Route - Sharma, Ashutosh; Srivastava, Ashok K.; Ahn, Byungmin (Metallurgical and Materials Transactions A: Physical Metallurgy and Materials Science, 2019)
A Cu-coated C nanofiber (Cu-CNF) composite is added to a Sn-3.5Ag alloy to fabricate a solder nanocomposite using mechanical stirring and a melting technique. The microstructural features of the samples, i.e., the β-Sn grain size and the distribution and thickness of the Ag3Sn intermetallic compound (IMC), are statistically measured. The wettability of the developed solders is tested on a Cu substrate by contact-angle and spreading-factor measurements. The experimental results indicate that the presence of up to 0.05 wt pct Cu-CNFs in the solder matrix reduces the β-Sn secondary dendritic arm spacing significantly. Additionally, the spread ratio and spread factor are improved to 93 and 96 pct, respectively, owing to the adsorption of surface-active CNFs in the solder matrix. Furthermore, the addition of 0.05 wt pct Cu-CNFs to the Sn-Ag (SA) alloy increases the microhardness, tensile strength, elongation percentage (El pct), and toughness by 40, 35, 11, and 33 pct, respectively.
Keywords: Elongation percentage; Mechanical stirring; Melting techniques; Microstructural features; Secondary dendritic arm spacing; Sn-3.5 Ag alloys; Spreading factor; Tensile behaviors